Business Model and Bank Risk in Indonesian Islamic Bank - Panji Patra Anggaredho; Rofikoh Rokhim (APMBA (Asia Pacific Management and Business Application), 2017)
This study aimed to analyze the relationship between business model of bank's risk in Islamic banks in Indonesia. Bank risk is represented by Z-score, while business model is represented in two ways, namely the portion of fee based income in income structure and the portion of non deposit funding in funding structure. This study analyzed panel data observed through the data 33 Islamic banks in Indonesia in 2005 to 2015. The results of this study concluded that the overall size of data portion of fee based income effect on the risk of bank, while the magnitude of portion of non deposit funding is not effect on bank's risk. Then, for robustness checks, We conducted a regression between variables to categorize Islamic banks into large and small Islamic banks. In the category of large banks, both fee based income and non deposit funding did not affect bank’s risk, while for banks categorized as small, the magnitude of portion of fee based income has an influence on risk of bank, while the magnitude of portion of non deposit funding has no effect the bank's risk.